Ciclo de protestos de 2013: construção midiática das performances de contestação - Camila Farias da Silva; Eduardo Georjão Fernandes (Ciências Sociais Unisinos)
This article presents a study on the cycle of protests of 2013, specifically on the forms of public manifestation of collective demands and their implications in the construction of meanings realized by the mainstream media. The purpose of this study is to identify the frameworks constructed by media vehicles regarding the public contentious performances composed by violent actions occurred in the cycle of protests of 2013. For that, the object of the study were the public contentious performances classified as violent and carried out in the demonstrations that took place in Porto Alegre on the demand of public transport from 1970 to 2013. Methodologically, the analysis of protest events was used from data collected in the research project “Regimes and Associative Repertoires: political opportunities and social organization in Brazil”, which is composed of news from Zero Hora newspaper about demonstrations of collective demands. Subsequently, an analysis of the coverage of Zero Hora about the cycle of protests of 2013 was made to identify the media construction of these performances. We analyzed the coverages for the events of March 27th, April 4th, June 13th and June 20th. The use of violent actions by demonstrators is perceived as a new phenomenon, in which large media vehicles, such as Zero Hora, use interpretive schemes already consolidated and previously constructed (to cover individual crime), in which violence is not identified as a contentious performance that composes a repertoire of action, but as an isolated and criminal action.